Quantifying Escherichia coli in household wastewater in Kuching, Sarawak - Ling, Teck Yee; Lee, Nyanti; Siew, Tuck-Fatt (Natural Resources, Environment and Development 2003, 2003)
Fecal pollution of surface water is a potential health hazard due to potential pathogens. This study aimed at quantifying an indicator bacteria, namely, Escherichia coli's loading from households of five residential areas into tributaries of Sg. Sarawak and also Sg. Kuap. Sampling of household wastewater was conducted for a duration of two months during dry season. Household survey was conducted to gather information on water consumption and demographic data. Results of this study indicated that water consumption ranged from 180 i/c/d to 371 l/c/d, wastewater flow ranged from 47.0 to 92.9 l/c/d. Mean temperature ranged from 28.0 to 29.5 Degree Celsius. Dissolved oxygen ranged from 1.96 to 3.40 mg/l. There is high variation in E.coli concentrations sampled during low, medium and high flow. Mean E.coli concentration increases as the age of the residence increases with the 20 years o9ld residence discharging E.coli concentration 13 times higher than that of less than a year old residence. However, in all housing areas, E.coli concentrations were in order of 10^6 cfu/c/d. With a population of 44,500 from the housing areas where the study was conducted, it is estimated that a total of 1.64 x 10^14 cfu of E.coli is discharge from the residential areas daily. To reduce the E. coli loadings into surface water around Kuching town, it is recommended that wastewater from septic tanks be channelled to central waste stabilization ponds.